Evaluation and management of overactive bladder: strategies for optimizing care - Willis-Gray, Marcella G (Res Rep Urol, 2016)
Overactive bladder (OAB) is a common condition affecting millions of men and women worldwide. It is an embarrassing condition with far-reaching consequences. Although many treatment options exist, no single treatment has been proven to be most effective. Often a combination of therapy is required to successfully manage OAB symptoms. In this review, we provide an overview of OAB, including risk factors for development of OAB; keys to diagnosis; therapeutic options including conservative and medical management, as well as treatments for refractory OAB; when to consider referral to a specialist; and resources for clinicians and patients. The aim of this review is to inform clinicians regarding OAB management in order to improve patient counseling and care.